The AGC Kinase YpkA Regulates Sphingolipids Biosynthesis and Physically Interacts With SakA MAP Kinase in Aspergillus fumigatus - Fabri, João Henrique Tadini Marilhano; Godoy, Naiane Lima; Rocha, Marina Campos; Munshi, Mansa; Cocio, Tiago Alexandre; von Zeska Kress, Marcia Regina; Fill, Taicia Pacheco; da Cunha, Anderson Ferreira; Del Poeta, Maurizio; Malavazi, Iran (Frontiers in Microbiology, 2019)
Sphingolipids (SL) are complex lipids and components of the plasma membrane which are involved in numerous cellular processes, as well as important for virulence of different fungal pathogens. In yeast, SL biosynthesis is regulated by the “AGC kinases” Ypk1 and Ypk2, which also seem to connect the SL biosynthesis with the cell wall integrity (CWI) and the High Osmolarity Glycerol (HOG) pathways. Here, we investigate the role of ypkAY PK1 in SL biosynthesis and its relationship with the CWI and the HOG pathways in the opportunistic human pathogen Aspergillus fumigatus. We found that ypkA is important for fungal viability, since the ΔypkA strain presented a drastically sick phenotype and complete absence of conidiation. We observed that under repressive condition, the conditional mutant niiA::ypkA exhibited vegetative growth defects, impaired germination and thermosensitivity. In addition, the ypkA loss of function caused a decrease in glycosphingolipid (GSL) levels, especially the metabolic intermediates belonging to the neutral GSL branch including dihydroceramide (DHC), ceramide (Cer), and glucosylceramide (GlcCer), but interestingly a small increase in ergosterol content. Genetic analyzes showed that ypkA genetically interacts with the MAP kinases of CWI and HOG pathways, mpkA and sakA, respectively, while only SakA physically interacts with YpkA. Our results suggest that YpkA is important for fungal survival through the regulation of GSL biosynthesis and cross talks with A. fumigatus MAP kinase pathways.